Does arch length preservation in mixed dentition children affect mandibular second permanent molar eruption? A systematic review and meta-analysis - Sivakumar Arunachalam; Indumathi Sivakumar; Jayakumar Jayaraman; Jitendra Sharan (BMC, 2021)
Abstract Background Arch length preservation strategies utilize leeway space or E-space in the mixed dentition to resolve mild to moderate mandibular incisor crowding. The purpose of this systematic review of the literature was to analyze the effects of arch length preservation strategies in on mandibular second permanent molar eruption. Methods A search for relevant articles published from inception until May 2020 was performed using PubMed/Medline, Cochrane databases, Clinicaltrials.gov, Google scholar and journal databases. Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were adopted for the conduct of the systematic review. Using RevMan 5.3 software, the most pertinent data were extracted and pooled for quantitative analysis with 95% confidence intervals. Heterogeneity was analyzed by using Cochran Q test and I squared statistics. Results A total of 5 studies involving 855 mixed dentition patients with arch length preservation therapy were included in the qualitative analysis. Pooled estimate of the data from two studies revealed 3.14 times higher odds of developing mandibular second molar eruption difficulty due to arch length preservation strategies using lingual holding arch (95% CI; OR 1.10-8.92). There was no heterogeneity found in the analysis. The certainty levels were graded as very low. Conclusions This systematic review demonstrates that arch length preservation strategies pose a risk for development of mandibular second molar eruption disturbances, but the evidence was of very low quality. Registration number: CRD42019116643.